2023
DOI: 10.1097/pxr.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Use of machine learning in the field of prosthetics and orthotics: A systematic narrative review

Abstract: Although machine learning is not yet being used in clinical practice within the fields of prosthetics and orthotics, several studies on the use of prosthetics and orthotics have been conducted. We intend to provide relevant knowledge by conducting a systematic review of prior studies on using machine learning in the fields of prosthetics and orthotics. We searched the Medical Literature Analysis and Retrieval System Online (MEDLINE), Cochrane, Embase, and Scopus databases and retrieved studies published until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It can significantly reduce knee extension muscle load during assisted squats, demonstrating its potential in easing physical strain (32,33). Though still emerging in prosthetics and orthotics, machine learning promises more efficient management of prostheses and orthoses (34).…”
Section: Comparing With Conventional Approachesmentioning
confidence: 99%
“…It can significantly reduce knee extension muscle load during assisted squats, demonstrating its potential in easing physical strain (32,33). Though still emerging in prosthetics and orthotics, machine learning promises more efficient management of prostheses and orthoses (34).…”
Section: Comparing With Conventional Approachesmentioning
confidence: 99%
“…While not yet integrated into standard clinical practice, several studies have demonstrated that wearable sensors, machine learning, and artificial intelligence could potentially be used in clinical practice to improve prosthetic care ( 97 100 ). However, many challenges still exist in integrating these technologies into clinical practice (e.g., privacy concerns with data collection and storage, maintaining software updates, data collection and storage, cost-effectiveness, clinician scope of practice, health equity) ( 101 105 ).…”
Section: Translation To Clinical Practicementioning
confidence: 99%
“…Advanced prosthetic limbs, such as the DEKA Arm (also known as the "Luke Arm") [107] and the BiOM T2 Ankle [108], use robotic technology to mimic natural limb movements and provide users with increased functionality and mobility [109].…”
Section: Robotic Prosthetics and Orthoticsmentioning
confidence: 99%